ANALYSIS OF FINANCIAL PERFORMANCE MEASUREMENT WITH THE BALANCED SCORECARD METHOD - Muhammad Nuur Farid Thoha Nuur Farid; Prananda Putra (SEAN Institute, 2022)
The complexity of today's business world necessitates a method for measuring a company's performance that is both precise and exhaustive. In this situation, the balanced scorecard is a useful tool. Balanced Scorecard is a performance measurement instrument that considers both financial and non-financial aspects. The Balanced Scorecard examines performance from four distinct perspectives: learning and development, internal company processes, the customer, and financials. For the purpose of this analysis, 2011-2021 PT HM Sampoerna Tbk data was utilized to examine the financial outlook. This research measures ROI, profit margin, operating ratio, customer satisfaction, innovation, and employee satisfaction. Based on the analysis's findings, it is evident that PT HM Sampoerna Tbk performs well overall. Financial measures such as return on investment (ROI), profit margins, and operating ratios have been rather strong. From the consumer's perspective, it demonstrates good performance, and customer satisfaction is fairly high. From an internal business perspective, the corporation has made positive adjustments. And from the perspective of an employee, the degree of learning and development is fairly adequate. According to the research findings, the Balanced Scorecard provides a better ordered and comprehensive picture.